Quasi-Infinite Adaptive Horizon Nonlinear Model Predictive Control. Issue 18 (2018) - Griffith, Devin W.; Patwardhan, Sachin C.; Biegler, Lorenz T.
Abstract: In this work we present a new method for calculating terminal conditions for nonlinear model predictive control (NMPC) that is non-conservative and scalable via the quasi-infinite horizon methodology. Then, we introduce adaptive-horizon NMPC, a new method for updating prediction horizon lengths online via nonlinear programming sensitivity calculations. Finally, we show how these methods work together to provide an adaptive horizon NMPC implementation for a quad-tank simulation example.